The Influence of Transformational Leadership on Employee Job Satisfaction at PT. Prima Raya Dinamika - Geraldi, Zefanya (Universitas Pamulang, 2024)
Employee loyalty is something that is difficult for companies to have. Feelings of dissatisfaction with their work make an employee disloyal towards their work. Transformational leadership is one factor that can increase employee job satisfaction. PT. Prima Raya Dinamika is a company that operates in the field of production machine spare parts and steel structures. Leader of PT. Prima Raya Dinamika increases employee job satisfaction by implementing transformational leadership. This research aims to analyze the influence of transformational leadership on employee job satisfaction at PT. Prima Raya Dynamics. The method used in this research is quantitative with a descriptive approach. This research applies a simple linear regression analysis test and coefficient of determination. The population in this research is all employees of PT. Prima Raya Dinamika has 11 employees, so sampling is not necessary. The results of this research show that transformational leadership has a positive effect on employee job satisfaction, based on the results of the coefficient of determination showing that job satisfaction is influenced by transformational leadership by 69.5%. So, the better the transformational leadership applied by PT leaders. Prima Raya Dinamika will increase employee job satisfaction. Suggestions submitted by the author to PT. Prima Raya Dinamika is by creating a forum that can accommodate employee aspirations regarding business development ideas and implementing reward and punishment methods to motivate employees to comply with company regulations.